Is alcoholism learned? Insights from the fruit fly. - Robinson, B.G.; Atkinson, N.S. (Current Opinion in Neurobiology, 2013)
Alcohol addiction is a complex, unique human disease. Breaking addiction down into contributing endophenotypes enables its study in a variety of model systems. The Drosophila model system has been most often used to study alcohol sensitivity, tolerance, and physiological dependence. However, none of these endophenotypes can account for the near-permanent quality of the addicted state. It has been recently discussed that addictive drugs may hijack the learning-and-memory machinery to produce persistent behavioral changes. Learning and memory is amenable to experimental study, and provides us with a window into how alcohol affects higher-order mental functions that are likely to contribute compulsive drug use. Here, we review the Drosophila literature that links alcohol-related behaviors to learning and memory.